1997
DOI: 10.1002/(sici)1099-1646(199703)13:2<151::aid-rrr447>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Dam and geomorphological influences on colorado river waterbird distribution, Grand Canyon, Arizona, USA

Abstract: Impoundment effects override natural, reach‐based channel geomorphology influences on seasonal waterbird distribution in Grand Canyon along the Colorado River downstream from Glen Canyon Dam. Large winter waterbird populations were rare or non‐existent prior to completion of Glen Canyon Dam in 1963, and pre‐dam summer breeding was rare. Post‐dam river corridor surveys of 13 geomorphological reaches from 1973 to 1994 detected 58 species of waterfowl, waders, shorebirds and piscivorous raptors, with a grand mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(16 citation statements)
references
References 34 publications
0
16
0
Order By: Relevance
“…1 of Patten et al [2001] in this feature). Other aspects of the geomorphology and ecology of this large desert river ecosystem are described by Howard and Dolan (1981), Johnson (1991), O'Conner et al (1994), Stevens et al ( , 1997a, and Bowers et al (1997). The river flows through 13 bedrock-controlled reaches that vary in characteristic width and depth (Schmidt andGraf 1990, Stevens et al 1997c).…”
Section: Study Areamentioning
confidence: 99%
“…1 of Patten et al [2001] in this feature). Other aspects of the geomorphology and ecology of this large desert river ecosystem are described by Howard and Dolan (1981), Johnson (1991), O'Conner et al (1994), Stevens et al ( , 1997a, and Bowers et al (1997). The river flows through 13 bedrock-controlled reaches that vary in characteristic width and depth (Schmidt andGraf 1990, Stevens et al 1997c).…”
Section: Study Areamentioning
confidence: 99%
“…Flow regulation has swamped geomorphic influences on biological organization in the aquatic domain of the river, reducing differences in benthic standing stock or species among various aquatic microhabitats (Stevens et al 1997b). In contrast, flow regulation has enhanced variation in biotic development on the various geomorphic microhabitats in debris fans in the riparian domain (Stevens et al 1995(Stevens et al , 1997a. Differential responses of the river ecosystem to flow regulation on the aquatic versus the riparian domains vastly complicate environmental management of focal species and habitats, creating challenging administrative tradeoffs Lovich and Melis 2007).…”
Section: Geology and Geomorphologymentioning
confidence: 99%
“…Prior to impoundment the canyon served as a long-linear migratory corridor for several native fish (e.g., Xyrauchen texanus razorback sucker and Ptychochelius lucius pikeminnow; Minckley 1973Minckley , 1991 and still provides that function for numerous migratory waterbirds (Stevens et al 1997a), and probably bats and monarch…”
Section: Annual Migratory Corridormentioning
confidence: 99%
“…Insect biomass declines dramatically downstream from the area of high primary production below Glen Canyon Dam (Stevens et al 1997a), indicating that other detritus sources are insufficient to support high insect production (i.e., the system does not change from autochthonously driven to allochthonously driven, maintaining high total food supplies for aquatic insects all along the river). That is, the whole downstream aquatic ecosystem appears to be driven by changes in aquatic primary productivity, particularly in the upper reaches.…”
Section: Aquatic Primary Productionmentioning
confidence: 99%
“…During model development, there was considerable debate about whether the natural system had a productive insect community (and, hence, about whether it could have supported substantial bird and fish communities). Stevens et al (1997a) reported little anecdotal evidence of pre-dam waterfowl from early river runners and other observers of the natural system. At present, there is a dramatic downstream decline in insect densities below the clear-water Glen Canyon Reach, suggesting no significant allochthonous replacement of detritus food supplies from terrestrial sources within the Canyon.…”
Section: Aquatic Insect Productionmentioning
confidence: 99%